Abner of Burgos: The Missing Link between Nasir al-Din al-Tusi and Nicolaus Copernicus? - Nosonovsky, Michael (Zutot, 2018)
The geometrical theorem known as the ‘Tusi couple’ was first discovered by Persian astronomer Nasir al-Din al-Tusi (1201–1274). The Tusi couple was believed to be discovered for Europeans by Nicolaus Copernicus (1473–1543) and it played an important role in the development of his planetary system. It has been suggested by Willy Hartner, that Copernicus borrowed it from al-Tusi, however, a particular way of transmission is not known. In this article I show that Spanish-Jewish author Abner of Burgos (1270–1340) was familiar with the Tusi couple and followed Tusi’s notation in his diagrams. This may provide a missing link in the transmission of the Muslim astronomic knowledge to Europe and advance our understanding of the European Renaissance as a multicultural phenomenon.